"Creating a family after battling cancer is exhausting and maddening": Exploring real‐world experiences of young adult cancer survivors seeking financial assistance for family building after treatment. Issue 12 (19th October 2018) - Benedict, Catherine; McLeggon, Jody‐Ann; Thom, Bridgette; Kelvin, Joanne F.; Landwehr, Michelle; Watson, Samantha; Ford, Jennifer S.
Abstract: Objective: Young adult (YA) cancer survivors who received gonadotoxic therapy are at risk for impaired fertility and/or childbearing difficulties. This study explored the experiences and financial concerns of survivors pursuing family building through assisted reproductive technology (ART) and adoption. Methods: Retrospective study of data collected from grant applications for financial assistance with family building. Grounded theory methodology using an inductive data‐driven approach guided qualitative data analysis. Results: Participants ( N  = 46) averaged 32 years old (SD = 3.4) were primarily female (81%) and married/partnered (83%). Four main themes were identified representing the (1) emotional experiences and (2) financial barriers to family building after cancer, (3) perceived impact on partners, and (4) disrupted life trajectory. Negative emotions were pervasive but were balanced with hope and optimism that parenthood would be achieved. Still, the combination of high ART/adoption costs, the financial impact of cancer, and limited sources for support caused extreme financial stress. Further, in the face of these high costs, many survivors reported worry and guilt about burdening partners, particularly as couples failed to meet personal and societal expectations for parenthood timelines. Conclusion: After cancer, YAs face numerous psychosocial and financial difficulties in their pursuits of family building when ART/adoption is needed to achieve parenthood. Survivors interested in future children may benefit from follow‐up fertility counseling post‐treatment including discussion of ART options, surrogacy, and adoption, as appropriate, and potential barriers. Planning for the financial cost and burden in particular may help to avoid or mitigate financial stress later on.